PENGGUNAAN DALIL PEMBELAAN TERPAKSA (NOODWEER) BERDASARKAN PASAL 49 AYAT (1) KITAB UNDANG – UNDANG HUKUM PIDANA (KUHP) TERHADAP TINDAK PIDANA PENGANIAYAAN - Selly Salsabila; Mukhlis R; Tengku Arif Hidayat (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Self-defense is a form of human defense in situations that threaten the safety of one'ssoul, decency and property. It is undeniable that this self-defense can also provide losses forperpetrators of criminal acts. Arrangements regarding self-defense are regulated in Article 49 ofthe Criminal Code. In that article it is said that a person who commits an act of defense for life,honor or property both for himself and for others cannot be punished. The purpose of this study,namely: First, criminal responsibility for perpetrators of criminal acts of persecution for self-defense according to Article 49 paragraph 1 of the Criminal Code when viewed from a justiceperspective, Second; the basis for the judge's consideration in the use of the forced defenseargument against the crime of persecution.This type of research can be classified as a type of normative research that examinesthe level of legal synchronization, because in this study the authors conduct research on legalsynchronization to what extent the existing written positive law is in accordance with itsapplication.In the results of research problems there are two things that can be concluded. First,actions committed by someone in the form of self-defense in a state of threat cannot be heldcriminally responsible. Second, there are differences in the judge's decision in passing hisdecision on the perpetrators of the crime of persecution for self-defence, where in the ManadoHigher Decision Number: 10/Pid/2013/PN.Mdo which does not apply Article 49 paragraph 1 ofthe Criminal Code. The author's suggestion, First: that in forming laws - laws provide moreexplanation of the formulation of articles in a more clear and straightforward manner so thatthere is no dualization of meaning by law enforcers and society. So that the meaning in Article49 paragraph 1 of the Criminal Code in particular can be conveyed and applied in cases of self-defense. Second, in making decisions, judges must uphold the principle of legal certainty, but theconcept of justice must be upheld in accordance with one of the objectives of the law itself. Inaddition, judges can also use other assistive sciences to become the rationale for knowing thesubjective elements of the offender.Keywords: Persecution – Forced Defense – Criminal Liability.